Resistividade elétrica de concretos contendo diferentes teores de cinza de casca de arroz - Hoppe, Tiago Fernandes (2005)
The durability of reinforced concrete structures derives from the protective effect provided by the concrete cover over the steel rebars. When the passivation of the steel is compromised, the whole structure is liable to corrosion phenomena, whose rate of propagation is mainly controlled by the electrical resistivity of the concrete between the anode and cathode and by the availability of oxygen at the cathode. The electrical resistivity of concrete is highly dependent on its physical and chemical characteristics. This study aimed at to investigate the influence of the content of rice husk ash (RHA) on the electrical resistivity of concrete and identify any correlations between electrical resistivity and compressive strength properties and changes in pore solution and pore structure. The mixtures in this study were prepared with water/binder ratios (w/b) of 0.35, 0.50 and 0.65 with RHA substitutions of 10%, 20% and 30% for cement. Samples with 50% blast furnace slag, 35% fly ash and a reference sample with 100% cement were also investigated. Electrical resistivity was determined using the four electrode method (Wenner s Method adapted for concrete). Tests of compressive strength, pore solution composition, pH e electrical condutivity, and mercury porosimetry were also performed. These indicate that that the age of the sample, the w/b ratio used and the mineral additions have a expressive effect on the electrical resistivity of concrete because of changes in the concrete pore structure and in the composition and volume of pore solution. Results show there is a exponential increase in concrete resistivity as the content of RHA grows. This is confirmed by the smaller size of the pore network and the lower specific conductivity of the pore solution, which show a sound correlation. The best results in electrical resistivity were obtained with content of 30% of RHA. The best cost/benefit ratio for compressive strength values of 65MPa and electrical resistivity of 30kΩ.cm was obtained with the use of 10% RHA and for compressive strength values of 65MPa and electrical resistivity of 60kΩ.cm, the best results were obtained with 20% RHA.